Bimetal catalyst and application thereof in thermal depolymerization of aliphatic polycarbonate
By designing an easily available and environmentally friendly bimetallic catalyst, the problems of low depolymerization efficiency and high cost of aliphatic polycarbonate in the prior art are solved, and efficient and economical chemical recycling of aliphatic polycarbonate to epoxy alkane monomers are achieved.
Patent Information
- Application Number
- CN202510482021.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-18
AI Technical Summary
When existing catalysts catalyzing the depolymerization of aliphatic polycarbonate into alkylene oxide monomers, there are problems such as synthesis, high cost or the use of toxic metals, making it difficult to achieve efficient and economical chemical recycling.
A class of bimetallic catalysts are designed to regulate metal species to change Lewis acidity by cooperating with ligands containing benzotriazole structures. The catalyst is composed of homogeneous or heterogeneous metals, simplifying the synthesis process and reducing toxicity, and are used for the thermal depolymerization of aliphatic polycarbonates.
Highly selective and efficient aliphatic polycarbonate depolymerization into alkylene oxides at low catalyst dosages. The catalyst is easy to obtain and environmentally friendly, and the products can be repolymerized directly, reducing resource waste and economic costs.
Smart Images

Figure CN120329358A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material degradation and recycling, and relates to the preparation of a type of bimetallic catalyst and its application in thermal depolymerization of aliphatic polycarbonate, so as to realize the cycle of polycarbonate to alkylene oxide monomer. Technical Background
[0002] Synthetic polymer materials mostly use petrochemicals as the main raw materials, and about 7% of oil and gas resources are used for the production of polymer materials every year. Plastics have the advantages of being cheap, easy to obtain, light, good performance and easy to process, and have become the main synthetic polymer materials. At present, the most widely used synthetic polymer plastics are polyolefins, mainly including polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC) and polystyrene. As of 2015, humans have produced a total of about 8.3 billion tons of plastics, of which about 6.3 billion tons have become waste, and only 9% have been recycled. Traditional polyolefin plastics have poor degradability, and the speed of microbial degradation through burial is very slow. They are easy to cause soil compaction in the soil, which is very harmful to the environment. They are also easily eaten by animals, causing secondary disasters. The special chemical composition structure of plastics is also difficult to recycle, and the economic efficiency is low, which makes waste plastics cause huge economic losses every year.
[0003] Polycarbonate is a polymer with customizable mechanical and thermal properties, including aliphatic polycarbonates with good biodegradability and aromatic polycarbonates with transparency, strong impact resistance, high rigidity and good thermal stability (Chem. Rev., 2021, 121, 10865-10907). Aliphatic polycarbonates prepared by alternating copolymerization of carbon dioxide and alkylene oxide have good biodegradability and have attracted much attention. However, due to the high price of alkylene oxide monomers, the practical application of this type of polycarbonate is seriously restricted. Therefore, if the efficient depolymerization chemical cycle of used aliphatic polycarbonates to alkylene oxide monomers can be achieved, its use cost can be greatly reduced, and it becomes a competitive degradable product.
[0004] There are many reports on the depolymerization of aliphatic polycarbonates at home and abroad. In 2013, Darensbourg et al. first reported the study of the catalytic conversion of poly(cyclopentene carbonate) to cyclopentene oxide monomer in solution, but a small amount of cyclic carbonate was generated simultaneously (Macromolecules 2013, 46, 5850). In 2017, our research group first achieved the complete degradation of carbon dioxide-based polycarbonates from biomass epoxy alkane monomers to the corresponding epoxy alkane monomers, but used a toxic binuclear chromium catalyst (Angew. Chem. Int. Ed., 2017, 56, 4862). Further research found that this catalyst could also catalyze various five-membered fused-ring epoxy alkanes (ACS Catal., 2021, 11, 8349; CN112851924A). In 2022, the research group of Wu Guangpeng used a bifunctional binuclear organoboron catalyst and potassium hydroxide to degrade poly(cyclopentene carbonate), and could completely convert poly(cyclopentene carbonate) into epoxy alkane monomers (Angew. Chem. Int. Ed., 2022, 61, e202210243). In 2022, the research group of Zhang Yuetao used an in-situ formed heterogeneous multinuclear zinc catalyst to selectively convert poly(cyclohexene carbonate) into the starting monomer at 150 °C for 9 hours (Chem. Sci., 2022, 13, 6283). In the same year, the research group of Williams used a heterobinuclear catalyst for the degradation of aliphatic polycarbonates, and obtained epoxy alkane monomers with a selectivity greater than 99% and a yield of up to 95% at 100-140 °C (J. Am. Chem. Soc., 2022, 144, 18444), and the depolymerization proceeded through a terminal scission mechanism. Our research group found that the selection of a mononuclear chromium catalyst could catalyze the thermal depolymerization of poly(cyclohexene carbonate) to cyclohexene oxide monomer without solvent and fractionation at 200 °C. Mechanistic studies showed that the catalytic depolymerization mainly occurred through random scission (Angew. Chem. Int. Ed. 2022, 61, e202204492). However, these catalytic systems generally suffer from problems such as difficult catalyst synthesis, high cost, or the use of toxic metals. The present invention aims to design a series of highly active, highly stable, easily prepared and non-toxic or low-toxicity bimetallic catalysts for the catalytic thermal chemical recycling of aliphatic polycarbonates to the starting monomer epoxy alkane. Summary of the Invention
[0005] The present invention provides a class of bimetallic catalysts and their application in efficiently catalyzing the degradation of aliphatic polycarbonates, realizing the efficient and highly selective degradation of aliphatic polycarbonates to epoxy alkanes at low catalyst dosages.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A class of bimetallic catalysts is formed by coordinating the same or different bimetals with ligands containing a benzotriazole structure; changing the type of central metal of the catalyst can regulate its Lewis acidity, thereby adjusting its catalytic activity; the general structural formula of the bimetallic catalyst is as follows:
[0008] In the formula, M 1 is Mg, Zn, Cr, Mn, Fe, Co, Cu or Ni;
[0009] M 2 is Mg, Zn, Cr, Mn, Fe, Co, Cu or Ni;
[0010] X is OAc, F, Cl, Br, I, OCH3, OCH2CH3, N3, CO2CF3 or CO2Cl3;
[0011] R is hydrogen, methyl, ethyl, n-propyl, isopropyl or tert-butyl.
[0012] A preparation method of a class of bimetallic catalysts:
[0013] (1) Preparation of ligands containing benzotriazole
[0014] Under the protection of inert gas, phenylbenzotriazole, paraformaldehyde and N,N′-dimethylethylenediamine are mixed, dissolved in an organic solvent, and then refluxed and cooled to room temperature; the product is recrystallized to obtain the ligand containing benzotriazole; the structural formula of the phenylbenzotriazole is The molar ratio of the phenylbenzotriazole, paraformaldehyde and N,N′-dimethylethylenediamine is 1~1.5:2~2.2:1~1.5; the organic solvent is ethanol or methanol; the reflux temperature is 50-80 °C, and the reflux time is 9~16 h;
[0015] (2) The preparation of the bimetallic catalyst is divided into the following three categories
[0016] (A) Preparation of bimetallic catalyst 1, where the bimetallic catalyst 1 refers to M 1 , M 2 Both are Fe or Ni;
[0017] The preparation method is as follows: Dissolve the ligand containing benzotriazole, perchlorate, acid and triethylamine in an organic solvent; after reflux reaction, cool to room temperature; remove the solvent under reduced pressure, wash, and dry in vacuo to obtain the homobimetallic catalyst 1;
[0018] The molar ratio of the ligand containing benzotriazole, perchlorate, acid and triethylamine is 1~1.2:2~4:2~5:2~4; the organic solvent is methanol, ethanol; the reflux reaction temperature is 50-80 °C, and the time is 24~48 h; the perchlorate is nickel perchlorate hexahydrate, iron perchlorate; the acid is HX;
[0019] (B) Preparation of bimetallic catalyst 2, where the bimetallic catalyst 2 refers to M 1 , M 2 Both are Mg, Zn, Cr, Mn, Co or Cu;
[0020] The preparation method is as follows: Dissolve the ligand containing benzotriazole and the alkyl metal in an organic solvent, and react at room temperature; after the reaction is completed, remove the solvent under reduced pressure, add an acid under inert gas protection, and react at room temperature until complete; wash the precipitate obtained from the reaction, and obtain the homobimetallic catalyst 2 after vacuum drying;
[0021] The molar ratio of the ligand containing benzotriazole to the alkyl metal is 1:2 to 5; the organic solvent is tetrahydrofuran, toluene, n-hexane or n-pentane; the reaction time is 12 to 24 h; the alkyl metal is M 1 R’ and M 2 R’; R’ is methyl, ethyl, n-propyl, isopropyl or tert-butyl; the acid is HX; the molar ratio of the ligand containing benzotriazole to HX is 1 to 1.2:1.6 to 2.7;
[0022] (C) Preparation of heterobimetallic catalyst, where the heterobimetallic catalyst refers to M 1 , M 2 Are different metals;
[0023] The preparation method is as follows: Under inert gas protection, dissolve the ligand containing benzotriazole and the metal salt in an organic
[0024] solvent
[0025] , then add the alkyl metal, and after reacting at room temperature, remove the solvent under reduced pressure, and obtain the heterobimetallic catalyst after vacuum drying;
[0026] The metal salt is M 2 X; the organic solvent is tetrahydrofuran, toluene, n-hexane or n-pentane; the alkyl metal is M 1 R’; R’ is methyl, ethyl, n-propyl, isopropyl or tert-butyl; the reaction time is 9 to 16 h; the molar ratio of the ligand containing benzotriazole, the metal salt and the alkyl metal is: 1 to 1.5:1 to 2:1 to 3.
[0027] A class of bimetallic catalysts is used for catalytic pyrolysis of aliphatic polycarbonate. The aliphatic polycarbonate is formed by alternating copolymerization of carbon dioxide and epoxide, and forms an epoxide monomer after catalytic pyrolysis; the structure of the aliphatic polycarbonate is as follows: Among them, n is an integer greater than zero;
[0028] The epoxide is 1, 2, 3, 4, 5 or 6;
[0029]
[0030] Further, the reaction temperature for catalytic pyrolytic depolymerization is 150 - 250 °C.
[0031] Further, the molar ratio of the bimetallic catalyst to the aliphatic polycarbonate (calculated according to its repeating unit) is 1:300 - 1:100000.
[0032] Further, the reaction time for catalytic pyrolytic depolymerization is 0.5 - 24 h.
[0033] Remarkable beneficial effects of the present invention:
[0034] (1) The catalyst has relatively high catalytic activity and can still effectively catalyze the depolymerization reaction of aliphatic polycarbonate at a relatively low concentration;
[0035] (2) The catalyst has good product selectivity and can obtain the product alkylene oxide with a relatively high yield;
[0036] (3) The catalyst is simple to synthesize, and the raw materials are cheap and easily available;
[0037] (4) The depolymerization ability of the catalyst can be regulated by changing the central metal of the catalyst;
[0038] (5) The obtained product has relatively high purity and can be directly used for repolymerization to produce aliphatic polycarbonate, realizing efficient recycling of waste plastics;
[0039] (6) By adding the solvent polyethylene glycol, the aliphatic polycarbonate and the catalyst can contact more uniformly, improving the degradation rate of the aliphatic polycarbonate;
[0040] (7) The used solvent polyethylene glycol is not easily consumed and does not react with other components in the system, and can be recycled. Description of the Drawings
[0041] Figure 1 1H NMR spectrum of cyclohexene oxide (CHO) as the product of Application Example 1 1 1H NMR spectrum.
[0042] Figure 2 1H NMR spectrum of the ligand containing benzotriazole in Example 1 1 1H NMR spectrum.
[0043] Figure 3 1H NMR spectrum of poly(cyclohexene carbonate) (PCHC) as the product of Application Example 1 1 1H NMR spectrum.
[0044] Figure 4 Mass spectrum of bimetallic catalyst I a 1H NMR spectrum.
[0045] Figure 5 is the mass spectrum of bimetallic catalyst I b .
[0046] Figure 6 is the mass spectrum of bimetallic catalyst I c .
[0047] Figure 7 is the mass spectrum of bimetallic catalyst I d . Detailed implementation mode
[0048] The present invention is illustrated by the following examples, but not all the examples feasible for the present invention.
[0049] Bimetallic catalyst I a , I b , I c , I d , and the names and numbers of cyclohexene oxide are shown in the following formula.
[0050]
[0051] The specific examples of the present invention are described in detail below in combination with the technical solutions (Table 1).
[0052] Example 1: Synthesis of bimetallic catalyst I a , and its preparation process is as follows:
[0053]
[0054] Under nitrogen protection, 2-(2'-hydroxy-5'-methylphenyl) benzotriazole (5.0 g, 22.20 mmol, 1.0 equiv.), paraformaldehyde (1.3 g, 44.40 mmol, 2.0 equiv.) and N,N'-dimethyl ethylenediamine (2.0 g, 22.20 mmol, 1.0 equiv.) were mixed and dissolved in 100 ml of ethanol, and then refluxed at 80 °C for 14 h and cooled to room temperature. The product was recrystallized from methanol to obtain a ligand containing benzotriazole. The ligand containing benzotriazole (500.0 mg, 0.89 mmol, 1.0 equiv.), nickel perchlorate hexahydrate (649.9 mg, 1.78 mmol, 2.0 equiv.), acetic acid (133.4 mg, 2.22 mmol, 2.5 equiv.) and triethylamine (224.8 mg, 2.22 mmol, 2.5 equiv.) were mixed and dissolved in 100 ml of methanol, refluxed at 80 °C for 24 h and cooled to room temperature. After removing the solvent under reduced pressure, it was washed with n-hexane several times and dried in vacuo to obtain bimetallic catalyst I a .
[0055] Example 2: Bimetallic Catalyst I b The synthesis is as follows:
[0056]
[0057] The synthetic method of the ligand containing benzotriazole is the same as that of the bimetallic catalyst I in Example 1 a Under nitrogen protection, the ligand containing benzotriazole (500.0 mg, 0.89 mmol, 1.0 equiv.) was dissolved in 15 ml of tetrahydrofuran, and then diethylzinc (329.3 mg, 2.67 mmol, 3.0 equiv.) was added. The reaction was carried out at room temperature for 12 h. After the reaction, the solvent was removed under reduced pressure. Under nitrogen protection, acetic acid (101.5 mg, 1.69 mmol, 1.9 equiv.) was added, and the reaction was carried out at room temperature until complete. It was washed with n-hexane several times and dried in vacuo to obtain bimetallic catalyst I b .
[0058] Example 3: Bimetallic Catalyst I c The synthesis is as follows:
[0059]
[0060] Bimetallic catalyst I c The specific preparation steps of are the same as those of the bimetallic catalyst I in Example 2 b except that the metal reagent diethylzinc is replaced with n-butylmagnesium.
[0061] Example 4: Bimetallic Catalyst I d The synthesis is as follows:
[0062]
[0063] The synthetic method of the ligand containing benzotriazole is the same as that of the bimetallic catalyst I in Example 1 a Under nitrogen protection, the ligand containing benzotriazole (500.0 mg, 0.89 mmol, 1.0 equiv.) and zinc acetate (163.1 mg, 0.89 mmol, 1.0 equiv.) were dissolved in tetrahydrofuran, and then n-butylmagnesium (123.0 mg, 0.89 mmol, 1.0 equiv.) was added. The reaction was carried out at room temperature for 12 h. After the reaction, the solvent was removed under reduced pressure and dried in vacuo to obtain bimetallic catalyst I d .
[0064] Application Examples 1 - 60:
[0065] According to the reaction conditions in the following table, Application Examples 1 - 60 were carried out. The bimetallic catalyst, aliphatic polycarbonate, and polyethylene glycol 2000 were successively added to a 25 mL dry Schlenk flask equipped with a magnetic stir bar. After reacting for the corresponding reaction time at the corresponding reaction temperature, a small amount of the reaction mixture was taken out for 1 1H NMR analysis of the conversion rate and selectivity. The conversion rate was calculated by NMR analysis, as well as the selectivity of the alkylene oxide product.
[0066]
[0067]
[0068] Note: The solvent was polyethylene glycol 2000, and the molar ratio of the polymer repeating unit to polyethylene glycol 2000 was 20:1.
Claims
1. A class of bimetallic catalysts, characterized in that, It is composed of the same or different bimetals and a ligand containing a benzotriazole structure; changing the type of central metal of the catalyst can regulate its Lewis acidity, thereby adjusting its catalytic activity; the general structural formula of the bimetal catalyst is as follows: where M 1 is Mg, Zn, Cr, Mn, Fe, Co, Cu or Ni; M 2 is Mg, Zn, Cr, Mn, Fe, Co, Cu or Ni; X is OAc, F, Cl, Br, I, OCH3, OCH2CH3, N3, CO2CF3 or CO2Cl3; R is hydrogen, methyl, ethyl, n-propyl, isopropyl or tert-butyl.
2. The preparation method of a class of bimetallic catalysts according to claim 1, characterized in that (1) Prepare a ligand containing benzotriazole Under the protection of inert gas, phenylbenzotriazole, paraformaldehyde and N,N′-dimethylethylenediamine are mixed, dissolved in an organic solvent, refluxed and then cooled to room temperature; the product is recrystallized to obtain a ligand containing benzotriazole; the structural formula of the phenylbenzotriazole is The molar ratio of the phenylbenzotriazole, paraformaldehyde and N,N′-dimethylethylenediamine is 1-1.5:2-2.2:1-1.5; the organic solvent is ethanol or methanol; the reflux temperature is 50-80 °C, and the reflux time is 9-16 h; (2) The preparation of the bimetallic catalyst is divided into the following three categories (A) Preparation of bimetallic catalyst 1, where the bimetallic catalyst 1 refers to M 1 , M 2 both being Fe or Ni; The preparation method is as follows: dissolve the ligand containing benzotriazole, perchlorate, acid and triethylamine in an organic solvent; cool to room temperature after reflux reaction; remove the solvent under reduced pressure, wash, and dry in vacuo to obtain the homobimetallic catalyst 1; The molar ratio of the ligand containing benzotriazole, perchlorate, acid and triethylamine is 1~1.2:2~4:2~5:2~4; the organic solvent is methanol or ethanol; the reflux reaction temperature is 50-80 °C, and the time is 24~48 h; the perchlorate is nickel perchlorate hexahydrate or iron perchlorate; the acid is HX; (B) Preparation of bimetallic catalyst 2, where the bimetallic catalyst 2 refers to M 1 , M 2 both are Mg, Zn, Cr, Mn, Co or Cu; The preparation method is as follows: dissolve the ligand containing benzotriazole and an alkyl metal in an organic solvent, and react at room temperature; after the reaction is completed, remove the solvent under reduced pressure, add acid under the protection of an inert gas, and react at room temperature until complete; wash the precipitate obtained from the reaction, and dry in vacuo to obtain the homobimetallic catalyst 2; The molar ratio of the benzotriazole-containing ligand to the alkyl metal is 1:2 to 5; the organic solvent is tetrahydrofuran, toluene, n-hexane or n-pentane; the reaction time is 12 to 24 h; the alkyl metal is M 1 R' and M 2 R'; R' is methyl, ethyl, n-propyl, isopropyl or tert-butyl; the acid is HX; the molar ratio of the benzotriazole-containing ligand to HX is 1 to 1.2:1.6 to 2.7; (C) Preparation of a heterogeneous bimetallic catalyst, where the heterogeneous bimetallic catalyst refers to M 1 and M 2 being different metals; The preparation method is as follows: under the protection of an inert gas, dissolve the ligand containing benzotriazole and a metal salt in an organic solvent, then add an alkyl metal, remove the solvent under reduced pressure after the reaction at room temperature is completed, and dry in vacuo to obtain a heterobimetallic catalyst; The metal salt is M 2 X; the organic solvent is tetrahydrofuran, toluene, n-hexane or n-pentane; the metal alkyl is M 1 R'; R' is methyl, ethyl, n-propyl, isopropyl or tert-butyl; the reaction time is 9 to 16 h; the molar ratio of the ligand containing benzotriazole, the metal salt and the metal alkyl is: 1 to 1.5: 1 to 2: 1 to 3 3. The class of bimetallic catalysts described in claim 1 is used for the catalytic pyrolysis of aliphatic polycarbonates, characterized in that, The aliphatic polycarbonate is formed by the alternating copolymerization of carbon dioxide and alkylene oxide, and forms alkylene oxide monomers after catalytic pyrolysis; the structure of the aliphatic polycarbonate is as follows: wherein, n is an integer greater than zero; The epoxyalkane is 1, 2, 3, 4, 5 or 6; 4. The application according to claim 3, characterized in that, The reaction temperature for catalytic pyrolysis is 150~250 °C.
5. The application according to claim 4 or 5, characterized in that, The molar ratio of the bimetallic catalyst to the aliphatic polycarbonate is 1:300~1:100000.
6. The application according to claim 6, characterized in that, The reaction time for catalytic pyrolysis is 0.5~24 h.
Citation Information
Patent Citations
Synthesis method of recyclable nitrogen-containing polycarbonate plastic
CN112851924A